ANALYSIS OF WORK DISCIPLINE AND JOB SATISFACTION ON LECTURER PERFORMANCE IN MEDAN CITY - Henry Aspan; Rozaini; Ari Prabowo; Ami Natuz Zahara (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research aims to determine and analyze the influence of work discipline and satisfaction on the performance of lecturers in Medan City. The type of research used in this research is associative research with a quantitative approach. The population in this study is the population in this study, namely all lecturers at private universities in Medan City. The sampling method in this research uses a probability sampling method with a simple random sampling technique, namely taking sample members from the population randomly without paying attention to the strata in the population, with a sample size of 60 respondents. Data collection methods were carried out by means of questionnaires and interviews. The data analysis method used is multiple linear regression analysis. Based on the research results obtained partially and simultaneously, it shows that work discipline and satisfaction with the performance of lecturers in Medan City. The results of the coefficient of determination test obtained an adjusted R square value of 0.818 (81.8%). This shows that the variablework discipline and job satisfactionable to explainlecturer performance was 81.8%,while the remaining 18.2% is influenced by other variables not examined inthis research.